Comparative Efficacy and Safety of Different Tenecteplase Doses With Alteplase in Acute Ischemic Stroke: A Systematic Review With Pairwise and Network Meta‐Analysis to Determine the Optimal Dose - Muhammad Hassan Waseem; Zain ul Abideen; Muhammad Haris Khan; Muhammad Fawad Tahir; Marium Khan; Hafsa Arshad Azam Raja; Ameer Haider Cheema; Sania Aimen; Muhammad Arslan Tariq; Javed Iqbal (Brain and Behavior)
ABSTRACT Background: Tenecteplase (TNK) is a novel thrombolytic agent gaining attention as an alternative to alteplase for treating acute ischemic stroke (AIS). This meta‐analysis evaluates the safety and efficacy of various TNK doses compared to alteplase, integrating recent randomized controlled trials (RCTs) and employing a frequentist network meta‐analysis to identify the optimal dose while addressing existing evidence gaps. Methods: Up until December 2024, PubMed, Cochrane Central, and ScienceDirect were searched. Using Review Manager 5.4.1 for pairwise meta‐analysis, the Risk Ratios (RR) with 95% Confidence Intervals (CI) were pooled under the random effects model. Additionally, R version 4.3.2 and the “netmeta” package were used to conduct a network meta‐analysis for various dosages of the two thrombolytic drugs. Results: Thirteen RCTs, pooling 9,044 patients, were included in the quantitative synthesis. TNK was associated with a statistically significant improvement in the excellent functional outcome (mRS 0–1) (RR = 1.04; 95% CI: [1.00, 1.08]; p = 0.03) compared to alteplase. No significant differences were observed between TNK and alteplase in terms of good functional outcome (mRS 0–2), poor functional outcome (mRS 5–6), major neurological improvement within 72 h, symptomatic intracranial hemorrhage (sICH), or mortality at 90 days. On network analysis, TNK 0.25 mg/kg showed significant improvement in excellent functional outcome (RR = 1.05, 95% CI: [1.01, 1.10]) and TNK 0.32 mg/kg in good functional outcome (1.30, 95% CI: [1.15, 1.48]) compared to alteplase. According to the P‐score ranking, TNK 0.25 mg/kg was ranked as the best for achieving an excellent outcome (P‐score = 0.86), and TNK 0.1 mg/kg as the worst (P‐score = 0.16). For symptomatic intracranial hemorrhage (sICH), alteplase 0.9 mg/kg was ranked as the best (P‐score = 0.71), and TNK 0.4 mg/kg as the worst (P‐score = 0.17). Conclusion: TNK (0.25‐0.32 mg/kg) demonstrates superior efficacy compared to alteplase in achieving functional outcomes for AIS, while alteplase remains safer regarding sICH. Optimal dosing favors TNK 0.25 mg/kg for efficacy, but safety considerations highlight the need for individualized thrombolytic selection.